Embodied Cognition: Taking the Next Step - Willems, Roel M.; Francken, Jolien C. (Frontiers in Psychology, 2012)
Recent years have seen a large amount of empirical studies related to ‘embodied cognition’. While interesting and valuable, there is something dissatisfying with the current state of affairs in this research domain. Hypotheses tend to be underspecified, testing in general terms for embodied versus disembodied processing. The lack of specificity of current hypotheses can easily lead to an erosion of the embodiment concept, and result in a situation in which essentially any effect is taken as positive evidence. Such erosion is not helpful to the field and does not do justice to the importance of embodiment. Here we want to take stock, and formulate directions for how it can be studied in a more fruitful fashion. As an example we will describe few example studies that have investigated the role of sensori-motor systems in the coding of meaning (‘embodied semantics’). Instead of focusing on the dichotomy between embodied and disembodied theories, we suggest that the field move forward and ask how and when sensori-motor systems and behavior are involved in cognition.